Exploring chemokine-mediated inflammatory responses in the testis and epididymis: insights into ectopic lymphoid organ formation - Hasan, Hiba; Justus Liebig University Giessen (My University, 2024)
Infertility is regarded as a worldwide problem where male factors account for approximately 50% of infertility cases. To date, a plethora of causes have been identified that can contribute to male infertility. Among the identifiable and potentially curable causes, infection and inflammation of the genital tract are the most frequent. Experimental autoimmune epididymo-orchitis (EAEO) is a mouse model of chronic testicular inflammation characterized by several symptoms reported also in cases of infertility in men. They include immune cell infiltration, elevation of pro-inflammatory and pro-fibrotic mediators (e.g. TNF, CCL2, activin A), impairment of spermatogenesis, destruction of the seminiferous tubule architecture as well as steroidogenic disturbances and fibrotic remodeling. CCL2 and its receptor CCR2 are well-characterized as a major chemokine signaling pathway involved in recruitment of monocytes and macrophages to sites of inflammation, where they contribute to tissue damage. Activin A, a pleiotropic factor whose production correlates with the severity of EAEO, has the capacity to modulate expression of chemokine receptors and ligands, specifically CCR2. Consequently, this study aimed to investigate how the chemokine network is changing during testicular inflammation in C57BL/6J (WT) and CCR2 deficient (Ccr2-/-) mice and how activin A can influence the expression of chemokines and their receptors. EAEO was induced in WT and Ccr2-/- mice and the testes were collected 50 days from the first immunization. The mRNA expression results show that the key chemokines and their receptors essential for macrophage trafficking are increased in EAEO testis, while the deficiency of CCR2 attenuates these changes. The expression of chemokine/chemokine-receptor-encoding genes was examined in human testicular biopsies. Accordingly, an increase in macrophages expressing CCR2 was demonstrated in human testicular biopsies with impaired spermatogenesis and focal leukocytic infiltrates. Importantly, the biopsies showing impaired spermatogenesis and concomitant focal leukocytic infiltration exhibited higher expression of CCL2 and CCR2 than control biopsies with no signs of inflammation and intact spermatogenesis. Moreover, using an in-vitro setup where bone marrow derived macrophages were used as a surrogate for testicular macrophages, it was revealed that activin A serves as an essential regulator of chemokine network expression. The inhibitor of activin A, follistatin, ameliorated the effects on the chemokine network. To add, macrophages were identified as the major cell population in EAEO testis expressing activin A. This implicates both CCR2 and activin A as potential therapeutical targets. Alterations in chemokine expression can predispose the affected tissue to immune cell infiltration, which can in some instances organize into aggregates that resemble lymph nodes in their structure, composition, chemokine expression as well as their functionality. Tertiary lymphoid organs (TLO) develop as a consequence of inflammation, which can be driven by a myriad of causes, such as infection and autoimmunity. Therefore, in the second part of the study, the putative development of TLO in the testis and epididymis under inflammatory conditions was investigated using two mouse models, i.e., sterile EAEO and acute UPEC-infection. Acute epididymitis is commonly caused by bacteria, where UPEC is a predominant pathogen. In the UPEC-infection model, different parts of the epididymis respond differently to the infection, so that the cauda epididymidis is selectively severely damaged displaying interstitial fibrosis, loss of epithelial integrity, increase in luminal diameter, immune cell infiltration and abscess formation. The results revealed that elements of TLO formation were not found in the EAEO testis, but they were detected in the inflamed cauda epididymidis. The cauda from EAEO mice and especially from animals infected with UPEC exhibited multiple elements and immune cells associated with TLO formation. UPEC-infected cauda epididymides showed the presence of distinct B and T cell zones, with high endothelial venules (HEV) in the T cell region containing CXCL13 within their lumen. Importantly, the B cells were proliferating, highlighting their possible role in performing germinal center reaction activities. In addition, the clustered immune cells demonstrated a reticular network, which could provide structural support and influence migration of immune cells and formation of antibodies. The B and T cells clustered into separate zones and this was in accordance with the high expression of TLO-related chemokines (Cxcl13, Ccl19 and Ccl21). Moreover, the genes critical for HEV formation (Tnf, Ltα) and maturation (Ltβ, Tnfsf14) were elevated. The cauda of EAEO mice also developed TLO and HEV, but in a less organized manner. Based on these results, it is speculated that the epididymis is susceptible to TLO formation under inflammatory conditions. Future studies investigating the impact of TLO development in the epididymis on male fertility are needed.
Keywords: ddc:610